Study of the influence of cobalt in the high formability of the Au-Fe system - Restrepo-Arcila, Sandra Milena; Echavarría-Velásquez, Alejandro Iván; Sánchez Londoño, Héctor Darío; Giraldo-Cadavid, Marco Antonio (Revista Facultad de Ingeniería, 2018)
Since ancient times, gold has been used due to its especial properties. Among those properties are the resistance to corrosion (for being noble), its high electrical and thermal conductivity, and also its conspicuous coloration. Gold has been applied in a diversity of subjects such as economy, jewelry, electronic circuits and odontology. The fascinating properties of gold are likely to improve with the preparation of alloys; among those, the Au-Fe alloys constitute some of the most studied nowadays. In this research, we present our results concerning the microstructure of the Au-Fe and Au-Fe-Co alloys. We fabricated gold based alloys with 25% (weight) Fe and then compared their structure and formability to Au-24.5Fe-0.5Co (% weight) to determine the role of cobalt in the alloy. An induction furnace with controlled atmosphere (argon) and conductor crucibles coated with zirconium silicate was used. The samples were characterized by three processes: as-cast, with heat treatment (HT) at T=900°C (1h and 3h) and as-cast centrifuged. The formability results for the as-cast samples revealed a 23% deformation (rolling mill) for the Au-25Fe versus a 62% for the Au-24.5Fe-0.5Co alloy (HT-1h; T=900°C), whilst for the as-cast centrifuged sample revealed a 75% deformation with ductile fracture for the Au-25Fe versus an 82% without fracture for the Au-24.5Fe-0.5Co alloy. This result is particularly promissory for the applications in jewelry, showing that the addition of cobalt increases the formability of Au-Fe alloys.